Analisis Kelayakan Finansial Wisata Air Terjun Kanto Lampo di Kabupaten Gianyar - Karya, Wayan Putri Prakanti; Restu, I Wayan; Wijayanti, Ni Putu Putri (Bumi Lestari; Vol 22 No 1 (2022)DO - 10.24843/blje.2022.v22.i01.p03, 2022)
Gianyar Regency has interesting tourist objects, one of which is Kanto Lampo Waterfall, located in Banjar Kelod Kangin, Beng Village, Gianyar District, Gianyar Regency. The origin of the name Kanto Lampo is that there are many Kanto Lampo trees that grow around the river. Supporting infrastructure facilities currently available at Kanto Lampo Waterfall are the availability of a reception office, gazebo/bale bengong, toilets, changing rooms/rinsing rooms, payment counters, bathing pools, food vendors, and a fairly large parking area. The number of tourist visits to the Kanto Lampo Waterfall tourist attraction from 2015 was 10,170 people and continued to increase every year until 2019 as many as 51,810 people. The research on the financial feasibility analysis of Kanto Lampo Waterfall tourism aims to determine the economic feasibility of a waterfall development business based on an economic-financial approach. This research took place from January to February 2021. Primary data were obtained from interviews, direct observation, and documentation in the field. Based on the data obtained, the business of the Kanto Lampo Waterfall tourist attraction obtained an NPV value for 10 years of investment of IDR 1,137,263,458,-. The IRR value is 38%. The BCR value obtained is 3.8. and the value of the Payback Period (PP) of 1.3 years shows that the payback period for the waterfall business is relatively fast. Keywords: Analysis; Beng; Economics; Feasibility; Tourism